Nutritional Qualities of Cocoa Pod Husk Treated with Bioconversion and or Provision of Nitrogen Sources in the Rumen - Syahrir Syahrir; Hartutik Hartutik; Kusmartono Kusmartono; Damry Damry (Media Peternakan, 2017)
The objective of this study was to investigate the effects of bioconversion using Phanerochaete chrysosporium and Pleurotus ostreatus and or inclusion of Moringa oleifera leaves and urea in the rumen on cocoa pod husk digestibility and fermentation in the rumen. There were 4 treatments tested: (1) 100% untreated cocoa pod husk (UCPH), (2) 55% UCPH + 43.7% M. oleifera + 1.30% urea (UCPHMU), (3) 100% bioconverted cocoa pod husk (BCPH), and (4) 55% BCPH + 44.5 M. oleifera + 0.5% urea (BCPHMU). Each of the treatments was replicated three times. Variables observed were dry matter and organic matter digestibilities and degradabilities, rumen VFA and ammonia concentrations, gas production, and calculated microbial biomass yields. Results indicated that the treatment increased dry matter (P<0.001) and organic matter (P<0.01) digestibility, with the highest for the BCPHMU and the lowest for the UCPH. The treatments also increased dry matter and organic matter degradability in the rumen (P<0.001), with the highest for the BCPHMU, followed by the UCPHMU, and then by the BCPH and the lowest was UCPH. The treatment affected rumen ammonia concentration (P=0.01), the highest value was found for the BCPHMU followed with UCPHMU and BCPH. Microbial biomass synthesis was affected (P<0.001) by the treatment and it was always higher when nitrogen was provided (UCPHMU and BCPHMU). Total VFA concentration or total gas production was higher for BCPHMU compared to other treatments. It can be concluded that nutritional quality of cocoa pod husk can be improved by either bioconversion with P. chrysosporium and P. ostreatus or inclusion of M. oleifera and urea in the rumen, but the best improvement can be obtained by the combination of bioconversion and provision of the nitrogen sources in the rumen.